Faktor - Faktor yang Mempengaruhi Behavioral Intention pada Fitur Toilet Tracking Aplikasi Mobile Transjakarta - Naura Artanti Shafwan Wibowo; Osly Usman; Ryna Parlyna (Ekopedia: Jurnal Ilmiah Ekonomi, 2026)
This study aims to analyze the factors influencing users' behavioral intention toward the Toilet Tracking feature on the Transjakarta mobile application to enhance user comfort and experience. The study extends the Technology Acceptance Model (TAM) by incorporating Personal Innovativeness, Self-Efficacy, and System Quality as independent variables, alongside Perceived Usefulness, Perceived Ease of Use, and Perceived Enjoyment as mediating variables influencing Behavioral Intention. A quantitative approach was employed using Partial Least Squares-Structural Equation Modeling (PLS-SEM) analyzed via SmartPLS 4.0 software. Data were collected through questionnaires distributed to 189 Transjakarta application user respondents. The findings demonstrate that Personal Innovativeness positively affects Perceived Usefulness, Self-Efficacy positively affects Perceived Ease of Use, and System Quality positively affects Perceived Enjoyment. Furthermore, Perceived Usefulness, Perceived Ease of Use, and Perceived Enjoyment significantly and positively influence Behavioral Intention, while also mediating the relationships between the independent variables and behavioral intention. These results indicate that enhancing system quality, perceived usefulness, ease of use, and enjoyable experiences increases users' intention to utilize the Toilet Tracking feature. This study provides valuable considerations for PT Transportasi Jakarta in developing innovative digital features.